Some Modified Versions of Durbin's h-Statistic - Tse, Y. K. (The Review of Economics and Statistics, 1985)
-This paper proposes a modified version of Durbin's h-statistic for testing residual correlation in a dynamic regression model. Finite sample properties of the new statistic, Durbin's h-statistic and Sargan's modified version of h are investigated by simulation.